Role of concrete bridges in sustainable development proceedings of the international symposium held at the University of Dundee, Scotland, UK on 3-4 September 2003 - Strasky, Jiri (Thomas Telford, 2003)
Themes covered include: innovative concrete bridges; design and construction; loading considerations; aesthetics of concrete bridges; whole life cycle economics for sustainability; and exploiting design.